Adapting and Implementing a Blended Collaborative Care Intervention for Older Adults with Multimorbidity: Quantitative and Qualitative Results from the ESCAPE Pilot Study - Josefine Schulze; Dagmar Lühmann; Jonas Nagel; Cornelia Regner; Christine Zelenak; Kristina Bersch; Christoph Herrmann-Lingen; Matthew M. Burg; Birgit Herbeck-Belnap (Behavioral Sciences)
Multimorbidity poses significant challenges for patients and healthcare systems, often exacerbated by fragmented care and insufficient collaboration across providers. Blended Collaborative Care (BCC) is a promising strategy to address care complexity by partnering care managers (CMs) with primary care providers (PCPs) and specialists. This study aimed to adapt and pilot a BCC intervention for patients aged 65+ with heart failure and physical–mental multimorbidity. Our objectives were to assess the feasibility of the study procedures, patient recruitment, participant satisfaction and acceptability, and to identify necessary adjustments for improving intervention delivery. We evaluated goal attainment and intervention fidelity through standardised electronic documentation by CMs, and patient acceptance and satisfaction through semi-structured interviews. A monocentric, one-arm pilot study involved nine patients with a mean of 6.7 contacts with their CM over three months. Patients’ health goals primarily focused on lifestyle changes and psychosocial support. The intervention was generally well-accepted, with no reported negative consequences. Difficulties in establishing working alliances with PCPs were a barrier to effective implementation. The analysis indicated the need for minor procedural adjustments. Next steps include launching the ESCAPE trial, a large randomised-controlled trial across different European healthcare systems and developing strategies to facilitate PCP involvement.